FINANCIAL MANAGEMENT OF INDIGENOUS VILLAGES IN LUWUS VILLAGE BATURITI TABANAN BALI - Sukarnasih, Desak Made; Wulandari, Ni Made Desi; Bhegawati, Desak Ayu Sriary (Journal of Management Small and Medium Enterprises (SMEs), 2024)
There are administrative and urban villages in Bali province. Together with administrative villages, it also has customary villages, which are settlements that retain the ancient autonomy of the area. The Tri Hita Karana element is one of the ancient village's distinguishing characteristics. The purpose of this study is to ascertain how Luwus Village, Baturiti Tabanan, and customary village Financial Management are impacted by Accountability, Transparency, and Tri Hita Karana. Using the census approach, this research is a quantitative study with a population of 36 people from the Traditional Village Management, Prajuru, and Kelian Banjar of Luwus Village, Baturiti Tabanan. Based on the significance of the statistical test results, the study's findings suggest that Tri Hita Karana, Accountability, and Transparency have a favorable and substantial impact on Financial Management. Keywords: Financial Management; Accountability; Transparency ; Tri Hita Karana